2008
DOI: 10.1055/s-2008-1034358
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Scutellaria baicalensis, Scutellaria lateriflora and Scutellaria racemosa: Genome Size, Antioxidant Potential and Phytochemistry

Abstract: The genus Scutellaria in the family Lamiaceae has over 350 species, many of which are medicinally active. One species, Scutellaria baicalensis, is one of the most widely prescribed plants in Traditional Chinese Medicine, used for neurological disorders, cancer and inflammatory diseases and has been the subject of detailed scientific study but little is known about the phytochemistry of other Scutellaria. The current study was designed to compare the medicinal phytochemistry of 3 species of Scutellaria used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
(39 reference statements)
2
30
1
1
Order By: Relevance
“…Of the three herbs S. racemosa had the highest wogonin content. Baicalin content was similar for the three herbs (Cole et al 2008), which differs from the findings of Makino et al (2008) who found baicalin content in the leaves and stems of S. baicalensis was insignificant in comparison to S. lateriflora. There was slightly more baicalin in S. baicalensis root than in S. lateriflora leaves (Makino et al 2008).…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Of the three herbs S. racemosa had the highest wogonin content. Baicalin content was similar for the three herbs (Cole et al 2008), which differs from the findings of Makino et al (2008) who found baicalin content in the leaves and stems of S. baicalensis was insignificant in comparison to S. lateriflora. There was slightly more baicalin in S. baicalensis root than in S. lateriflora leaves (Makino et al 2008).…”
Section: Introductioncontrasting
confidence: 98%
“…For example, in common with many other Scutellaria species, S. lateriflora and S. baicalensis have similar phytochemical constituents, although in different ratios and quantities, which may explain the differing traditional uses amongst Scutellaria species (Cole et al 2008). Using HPLC, Cole et al (2008) quantitatively compared the content of flavonoids scutellarin, wogonin, baicalin and baicalein in aerial parts of S. lateriflora, S. baicalensis and S. racemosa grown in identical conditions. S. lateriflora contained the highest amount of baicalein while S. baicalensis contained 800 times more scutellarin than the other two herbs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various strategies have been developed which could increase the accumulation of biomass and biosynthesis of secondary metabolites in plant cell and organ cultures (Cole et al 2007). Attempts to produce phytochemicals of Scutellaria species through tissue culture have been reported earlier for S. baicalensis, S. columnae, S. lateriflora and S. racemosa (Seo et al 1993;Nishikawa and Ishimura 1997;Stojakowska and Kisiel 1998;Cole et al 2008). Previous studies describe the successful establishment of shoot regenerating calli and whole plants of S. altissima and these have been found to produce important secondary metabolites (GrzegorczykKarolak et al 2013(GrzegorczykKarolak et al , 2015.…”
Section: Introductionmentioning
confidence: 98%
“…Although S. lateriflora is a popular herb in western herbal medicine and contained in many herbal formulations (Joshee et al, 2002), particularly for anxiety and stress, relatively few scientific studies of this herb exist (Cole et al, 2008).…”
Section: American Skullcap (Scutellaria Lateriflora L)mentioning
confidence: 99%
“…In common with many other Scutellaria species, S. lateriflora and S. baicalensis have similar phytochemical constituents, although in different ratios and quantities, which may explain the differing traditional uses amongst Scutellaria species. For instance, S. baicalensis contains 800 times more scutellarin than S. lateriflora (Cole et al, 2008). Although S. baicalensis is most commonly used for inflammation (Joshee et al, 2002) both S. lateriflora and S. baicalensis have been found to inhibit cyclooexgenases in vitro Jia et al, 2007).…”
Section: S Lateriflora Is the Practitioner's Choice For Treating Anxietymentioning
confidence: 99%